Significance of MHD Radiative Non-Newtonian Nanofluid Flow towards a Porous Channel: A Framework of the Casson Fluid Model - N. Thamaraikannan; S. Karthikeyan; Dinesh Kumar Chaudhary (Journal of Mathematics)
The effect of various parameters in the unsteady pulsating flow of radiative hydromagnetic Casson nanofluid through a porous channel is investigated. The governing equations were nondimensionalized by applying suitable transformations. The perturbation technique was employed to solve the resulting similarity equations. The velocity and temperature fields are illustrated for several pertinent flow parameters. The fluid velocity has been enhancing for higher values of the frequency parameter, Casson fluid parameter, nanoparticle volume fraction, and Darcy number. The reverse impact is observed for larger values of the Hartmann number. The result reveals that adding the nanoparticles has enhanced the heat transfer of the base fluid as the nanoparticles increase the heat conductivity. Furthermore, it is noticed that the temperature profile decreases rapidly for higher values of the cross Reynolds number and the radiation parameter. Finally, an excellent agreement between the current results and previous results is obtained by comparing with the available limiting results in the literature.